Israel Gohberg and Friends On the Occasion of his 80th Birthday - Bart, Harm.; Hempfling, Thomas; Kaashoek, Marinus A.; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2008)
This book is dedicated to Israel Gohberg on occasion of his 80th birthday on August 23, 2008. It is an expression of esteem and friendship for a great mathematician, a remarkable person and an inspiring colleague. The book contains reflections by Gohberg himself on his own mathematical activities and those of others. It also includes contributions of colleagues and co-workers, both from his time in the Soviet Union and from when he lived and worked in the West. The contributions in question are not mathematical research papers but focus on the man Israel Gohberg and are intended for a wide audience. To be found are letters, speeches, laudatios and reminiscences which, together, present an attractive picture of the way in which Israel Gohberg in the past four to five decades influenced the lives of many mathematicians. Biographical material such as a curriculum vitae, a list of publications, a list of Ph.D. students and information about honorary doctoral degrees is also included.
Mathematical Tales and Philosophical-Mathematical Tales -- Mathematical Tales -- Philosophical-Mathematical Tales A Personal Account -- Our Dad’s Mathematics -- Work and personalia -- Curriculum Vitae of Israel Gohberg -- List of Publications of Israel Gohberg -- List of Graduate Students of Israel Gohberg -- Reference -- Election Moldavian Academy of Sciences -- A Review of the Mathematical Work of Israel Gohberg up to 1998 -- Gohberg’ Mathematical Work in the Period 1998–2008 -- The Nathan and Lily Silver Chair -- Gohberg Miscellanea: Celebrating the 60th birthday -- Gohberg Miscellania -- Celebrating the 70th Birthday -- Speeches Given at the Conference Dinner in Celebration of Israel Gohberg’s 70th Birthday -- About Colleagues and Friends -- Opening Address Toeplitz Memorial Conference -- David Milman (1912–1982) -- Biography of M.S. Livšic -- Odessa Reminiscences -- Opening Address -- Mark Grigorievich Krein: Recollections -- Heinz Langer and his Work -- Vladimir Maz’ ya: Friend and Mathematician. Recollections -- Reminiscences of Béla Sz?kefalvi-Nagy -- Peter Lancaster, my Friend and Co-author -- On Joint Work with Harry Dym -- In Memoriam Seymour Goldberg (1928–2004) -- In Memoriam Georg Heinig (1947–2005) -- Recollections: Vasile Grigorievich Ceban, on his 90th Birthday -- Heinz Langer, my Friend and Colleague Recollections. After Dinner Speech -- Our Meetings with Erhard Meister -- Honorary Doctorates: Laudatios and Replies -- VI.1.The Technische Hochschule at Darmstadt, Germany -- VI.2. The Vienna University of Technology at Vienna, Austria -- VI.3. West University of Timi?oara in Rumania -- VI.4. The Moldova State University at Chisinau, Moldova -- VI.5. Balti State University “Alecu Russo” at Balti, Moldova -- 6.6. The Israel Institute of Technology, Haifa, Israel -- Festschrift 2008 -- Collaborating with Israel Gohberg: Some Personal Thoughts -- My Collaboration with Israel Gohberg -- Israel Gohberg: a Teacher and a Friend -- Linear and One-dimensional -- Rehovot Days Redux2 -- Israel Tsudikovich: My Older Colleague and Older Friend -- Eight Friends -- Israel Gohberg and Engineering -- Professor at Amsterdam: Thank you Israel! -- IG and Me -- To Israel -- From a Young Student to an Older One -- What About Stability? -- Israel Gohberg and his Influence on my Mathematical Life -- The First Visits of Israel Gohberg to Karl-Marx-Stadt (Chemnitz) -- My Gohberg Encounters -- Becoming a Co-author.
Keywords: Mathematics; History; History of Mathematical Sciences